The influence of leadership styles, organizational changes on employee performance with an environment work as an intervening variable at pt. Bank sumut binjai branch - ICHSAN, REZA NURUL; NASUTION, LUKMAN; SINAGA, SARMAN; MARWAN, DHONI (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to find out whether the Leadership Style and Organizational Influence on Employee Performance with The Work Environment As Intervening Variables. The samples used in this study amounted to 47 employees of PT. Bank Sumut Binjai Branch. The data was obtained by distributing questionnaires about Leadership Style, Organizational Change, Employee Performance and Work Environment by distributing to 47 employees who had been respondents. Data analasis using Path Analysis (A combined model between multiple regression and intervening models). The results showed a direct influence of Leadership Style (X1) affecting Employee Performance (Y) by 0.337 or 34%. Organizational Change (X2) affects Employee Performance (Y) by 0.467 or 47%. Leadership Style (X1) affects the Work Environment (Z) by 0.289 or 29%. Organizational Change (X2) affects the Work Environment (Z) by 0.331 or 33%. Employee Performance (Y) affects the Work Environment (Z) by 0.454 or 45%. This research also showed the indirect influence of Leadership Style on Employee Performance Through Work Environment by 0.152 or by 15%. And the indirect influence of Organizational Changes on Employee Performance through the Work Environment is 0.212 or 21%.